The relationship between coping styles and benefit finding of Chinese cancer patients: The mediating role of distress. (June 2018) - Liu, Zhunzhun; Zhang, Lanfeng; Cao, Yuerong; Xia, Wenkai; Zhang, Liying
Abstract: Purpose: To identify the relationship of medical coping styles and benefit finding in Chinese early-stage cancer patients by preliminary pilot study. Method: Three hundred and fifty one cancer patients were recruited from the Affiliated Jiangyin Hospital of Southeast University medical college and the Nantong Tumor Hospital in this study. Measurements were Chinese Benefit Finding Scale, Medical Coping Modes Questionnaire- Chinese version and Distress Thermometer. Regression analysis and pathway analysis were employed to identify the correlation of medical coping styles and benefit finding, and the mediating role of distress. Results: Hierarchical regression analyses showed that confrontation coping style explained 24% of the variance in benefit finding, controlling for demographics and medical variables. While confrontation and resignation coping styles explained 10% and 6% of variance in distress separately. Pathway analyses implied that distress was found to mediate the effect of confrontation coping style on benefit finding in our study. Conclusions: Our study suggested an indirect association between medical coping styles and benefit finding, and a negative correlation of distress to medical coping styles and benefit finding. These results indicated that medical coping styles could influence benefit finding through distress. Highlights: There was a need to assess the implied 'causal' associations between coping modes, benefit finding and distress. Drawing on data from cross-section designed study, this paper examined the temporal relationships between the development of distress in relation to medical coping modes and subsequent benefit finding.